2019
DOI: 10.3389/fphys.2019.00815
|View full text |Cite|
|
Sign up to set email alerts
|

The Spectrum of SPTA1-Associated Hereditary Spherocytosis

Abstract: Hereditary spherocytosis (HS) is the most common red blood cell (RBC) membrane disorder causing hereditary hemolytic anemia. Patients with HS have defects in the genes coding for ankyrin ( ANK1 ), band 3 ( SLC4A1 ), protein 4.2 ( EPB42 ), and α ( SPTA1 ) or β-spectrin ( SPTB ). Severe recessive HS is most commonly due to biallelic SPTA1 mutations. α-spectrin is produced in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 20 publications
0
40
1
Order By: Relevance
“…Therefore, a single heterozygous mutation in the SPTA1 gene can still synthesize enough α-spectrin to balance β-spectrin and maintain the erythrocyte skeleton, without obvious abnormal erythrocytes in the peripheral blood and clinical manifestations. Only homozygous or compound heterozygous mutations might be involved in the pathogenesis of recessive spectrum protein-deficient HS, and its severity is associated with the amount of α-spectrin in the erythrocyte membrane skeleton [19,20]. The production of <25% α-spectrin results in diseases [21].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a single heterozygous mutation in the SPTA1 gene can still synthesize enough α-spectrin to balance β-spectrin and maintain the erythrocyte skeleton, without obvious abnormal erythrocytes in the peripheral blood and clinical manifestations. Only homozygous or compound heterozygous mutations might be involved in the pathogenesis of recessive spectrum protein-deficient HS, and its severity is associated with the amount of α-spectrin in the erythrocyte membrane skeleton [19,20]. The production of <25% α-spectrin results in diseases [21].…”
Section: Discussionmentioning
confidence: 99%
“…EPB42, erythrocyte membrane protein band 4.2, was an ATP-binding protein which may regulate the correlation of protein 3 with ankyrin. It was reported that EPB42 could manipulate the shape and mechanical property of erythrocyte and have a high association with hereditary spherocytosis [40,41]. SLC4A1, the protein encoded by this gene was part of the anion exchanger family and was expressed in the erythrocyte plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…At initial consultation, prednisone wean was initiated and diagnosis was re‐evaluated by genetic testing, since reliable RBC phenotypic evaluation was not feasible due to his transfusion dependency. HHA gene panel demonstrated that he had autosomal recessive HS with biallelic SPTA1 mutations (a premature termination: c.5102A>T; p.L1701* in trans to the low expression PRAgue allele α LEPRA ) 6 . After discussions with the family regarding risks and benefits of partial versus total splenectomy, a partial splenectomy was performed.…”
Section: Consultation With the Hematologistmentioning
confidence: 99%
“…Partial or total splenectomy in HS results, respectively, in improvement or complete resolution of anemia, except for the rare cases of complete alpha‐spectrin deficiency, due to biallelic null SPTA1 mutations, which have no improvement with splenectomy and are currently treated either with chronic transfusions and chelation or with hematopoietic stem cell transplant (HSCT) 6 . Based on data being collected from registries for rare diseases, splenectomy for severe PKD or CDA‐II may just offer a temporary transfusion relief during childhood, but typically does not correct anemia.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation